Prognostic significance of NEK2 in human solid tumors: a systematic review and meta-analysis. Issue 1 (18th January 2019) - Wang, Xichen; Chen, Kang; Liu, Haipeng; Huang, Zeping; Chen, Xiao; Yin, Lanning
Abstract : A consensus about the prognostic role of NIMA-related kinase 2 (NEK2) expression in various solid tumors has not been made yet. Thus, this meta-analysis aimed to systematically assess the prognostic role of NEK2 expression in patients with solid tumors. The eligible studies were identified through searching PubMed, Web of Science, and EMBASE. The hazard ratios (HRs) with their corresponding 95% confidence intervals (CIs) were used to evaluate the link between NEK2 overexpression and overall survival (OS) and disease-free survival/recurrence-free survival (DFS/RFS) of patients with solid tumors. A total of 17 studies with 4897 patients were included in this meta-analysis. Among these studies, all of them explored the association between NEK2 expression and OS of patients with solid tumors. Our pooled analysis indicated that NEK2 overexpression was significantly related to adverse OS (HR = 1.66; 95% CI: 1.38–2.00; P = 0.001). Additionally, there were six studies with 854 patients that investigated the association between NEK2 expression and DFS/RFS. Our pooled result indicated that there was a substantial relationship between NEK2 overexpression and poorer DFS/RFS (HR = 2.00; 95% CI: 1.61–2.48; P = 0.003). In conclusion, our meta-analysis indicated that NEK2 may be a useful predictor of prognosis and an effective therapeutic target in solid tumors. Nevertheless, more high-quality studies are warranted to further support our conclusions because of several limitations in our meta-analysis.